MONITORING PROGRESS KERJA PEGAWAI DIREKTORAT KEBERLANJUTAN KONSTRUKSI DENGAN METODE RAPID APPLICATION DEVELOPMENT (RAD) BERBASIS WEB - Al-Ayufi Solehudin1; Nur Wahyu; Nurul Fariz; Roeslan Djutalov (Journal of Research and Publication Innovation, 2024)
Information Technology in the current era is developing rapidly and is crucial to facilitate and support the company's processes in achieving its goals. In order to improve the company's sustainability, employees must work professionally, carrying out tasks assigned by superiors, and taking responsibility for completing every assigned task. The Directorate of Construction Sustainability is one of the directorates under the Directorate General of Construction Development, Ministry of Public Works and People's Housing. The Directorate of Construction Sustainability is tasked with formulating policies, drafting regulatory products, fostering implementation, and overseeing sustainability in the construction sector. In carrying out the tasks as stipulated in Article 518, the leadership of the Directorate of Construction Sustainability currently faces challenges in monitoring the work progress undertaken by employees, and there is no existing system to address this issue. Considering the description of the problems and the needs of the Directorate of Construction Sustainability, it is hoped that students can facilitate the leadership by creating a web-based employee work progress monitoring information system. This system will enable the monitoring of employee performance or the deadline for completing tasks assigned by the leadership. Consequently, the leadership can assess the performance of employees in the Directorate of Construction Sustainability office.